POLLEN MORPHOLOGICAL DIVERSITY OF ASTERACEAE SPECIES IN THE TADULAKO UNIVERSITY CAMPUS AREA - Budiono, Yudhistira Kristinov; Rasyiid, Mustafid; Musa, Khairul; Iqbal, Moh. (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2025)
This study aims to explore the morpho-anatomical diversity of pollen from various plant species belonging to the Asteraceae family within the Tadulako University area. Flower samples were collected using an exploration method and prepared for palynological analysis using a modified acetolysis technique. Six Asteraceae species were identified: Tridax procumbens L., Cyanthillium cinereum (L.) H.Rob., Synedrella nodiflora (L.) Gaertn., Eleutheranthera ruderalis (Sw.) Sch.Bip., Porophyllum ruderale (Jacq.) Cass., and Chromolaena odorata (L.) R.M.King & H.Rob. The study revealed significant differences in pollen morphology, particularly in shape (spheroidal), aperture number (3–4 colporates), ornamentation (echinate vs. lophate), and size. Pollen size ranged from 21.29 µm to 35.66 µm (equatorial diameter) and wall thickness ranged from 2.16 µm to 4.82 µm. These variations serve as reliable taxonomic markers for distinguishing species at both genus and species levels. This research provides valuable insights into the biodiversity and evolutionary adaptations of the Asteraceae family and supports the use of palynological data in systematic botany.